Evaluation and comparison of exergy-based resource consumption for fly ash utilisation in a cement clinker production system and landfill disposal. (29th October 2021) - Wang, Yanjing; Cui, Suping; Liu, Yu; Sun, Boxue; Gong, Xianzheng; Gao, Feng
It is unclear whether the utilisation of fly ash as valuable resource is preferable to landfill disposal from the resource perspective. The objective of this study was to evaluate and compare the resource consumption of fly ash utilisation in a cement clinker system compared to landfill disposal. The results indicated that when fly ash is used as substitute for clay, resource-saving potential of clinker system reached 147.47 MJ/t-clinker. The comparative analysis displayed that exergy-based resource consumption is reduced by 2, 020.48 MJ when 1 t fly ash used in a clinker system instead of landfill.